Risk Factors of Functional Dyspepsia, Gastrointestinal Reflux Disease and Non-Erosive Reflux Disease - Malik, Ayesha; Ud Din, Rafi; Asif, Mahrosh; Naeem, Iqra; Habib, Aamir; Khan, Asma Arshad (Scripta Medica, 2024)
Background/Aim: Functional dyspepsia, erosive and non-erosive gastroesophageal reflux disease (GERD) present a major health burden, adversely effecting quality of life. A range of factors are hypothesised to have a positive and negative influence on these diseases. This study aimed to explore the risk factors of functional dyspepsia, gastrointestinal reflux disease and non-erosive reflux disease and its subgroups. Methods: A cross-sectional study was conducted at Combined Military Hospital (CMH), Lahore, Pakistan, from January to June 2024. Two hundred and twenty-two patients were included and interviewed to fill a tri-section questionnaire comprising a self-designed comprehensive health survey, food frequency questionnaire, gastroesophageal reflux disease questionnaire (GERD-Q), Rome IV criteria, and hospital anxiety and depression scale (HADS). Results: Participants consisted of 70 controls, 38 GERD, 24 non-erosive reflux disease, 56 functional dyspepsia and 24 overlap reflux-dyspepsia syndrome patients. Subgroups included symptomatic and asymptomatic erosive oesophagitis, epigastric pain syndrome, postprandial distress syndrome and overlap syndrome. Older age, higher BMIs, male gender, low vegetable and yogurt intake, smoking, frequent red meat, high tea/caffeine intake, no postprandial exercise and a short dinner sleep interval were risk factors for GERD and symptomatic erosive esophagitis. Low BMI, female gender and anxiety were strongly associated with functional dyspepsia and non-erosive reflux disease. Conclusion: Age, BMI, gender, tobacco, anxiety, depression, dietary habits and food frequencies are significant risk factors of dyspepsia and reflux disease.
Keywords: Anxiety; Depression; Dyspepsia; Gastroesophageal reflux; Risk factors